Case Report: Novel Splicing Variant in SH2D1A in a Patient With X-Linked Lymphoproliferative Syndrome Type 1 - Kwon, Won Kyung; Kim, Jee Ah; Park, Jong-Ho; Kim, Doo Ri; Park, Su Eun; Kim, Yae Jean; Yoo, Keon Hee; Jang, Ja-Hyun; Kang, Eun Suk (Frontiers in Pediatrics, 2022)
X-linked lymphoproliferative disease type 1 (XLP1), an X-linked recessive genetic disorder, is associated with primary immunodeficiency. Patients with XLP1 are susceptible to Epstein–Barr virus (EBV) infection. SH2D1A gene is known as the causative gene. We found a novel hemizygous variant of SH2D1A, c.162_201+31delinsTACAAGGACATATACA, from a 5-year-old male patient who had been diagnosed with EBV infection and Hodgkin's lymphoma. In targeted next-generation sequencing (NGS), complex variants at exon 2 were not consistently identified with two software programs. They showed a soft-clipped read pattern. The variant had a 71-bp deletion and a 16-bp insertion across exon 2 as confirmed by direct sequencing. As the variant was located within the exon–intron boundary, two aberrant transcripts were shown by RNA study. Although NGS method has a limitation in detecting large deletion/duplication variants, proper bioinformatics pipeline and careful review of data might enable the detection of complex variants.